Tension band suture technique for the fixation of a displaced posterolateral acromion process fracture with subacromial impingement. Issue 3 (2nd March 2021) - Yu, Jiakun; Wynell-Mayow, William; Tang, Quen; Babu, Victor
Abstract : An adult old cyclist presented to our hospital and was referred to the orthopaedic department with a left shoulder posterolateral acromion avulsion fracture and subacromial impingement demonstrated on X-ray and CT. This highly unusual fracture pattern was treated by open reduction and internal fixation with cannulated screws and a tension band suture technique. This fracture went onto successful union with full range of motion and good patient-reported outcome measures by the Oxford Shoulder Score at 3 months. Informed consent was taken for the following case report.